2011
DOI: 10.1152/japplphysiol.00625.2010
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary gastrin 17 increases cardiac perfusion and function through autonomic nervous system, CCK receptors, and nitric oxide in anesthetized pigs

Abstract: The release of gastrointestinal hormones has been reported to modulate reflex cardiovascular responses caused by gastric distension, although the role played by gastrin 17 is as yet unknown. The present study was therefore planned to determine the primary in vivo effect of gastrin 17 on coronary blood flow and cardiac function and the involvement of autonomic nervous system, CCK1/2 receptors, and nitric oxide (NO). In 40 anesthetized pigs, gastrin 17 was infused into the left anterior descending coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…The role of CCK2R in protecting against IRI is controversial. In the heart, gastrin 17 increases cardiac perfusion and function through CCK2R in anesthetized pigs 10. In the present study, we found that C1988, a selective inhibitor of CCK2R, abolished the gastrin‐induced cardioprotective effects; therefore, the potent cardioprotective role of gastrin in the I/R‐injured heart is likely mediated through CCK2R.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…The role of CCK2R in protecting against IRI is controversial. In the heart, gastrin 17 increases cardiac perfusion and function through CCK2R in anesthetized pigs 10. In the present study, we found that C1988, a selective inhibitor of CCK2R, abolished the gastrin‐induced cardioprotective effects; therefore, the potent cardioprotective role of gastrin in the I/R‐injured heart is likely mediated through CCK2R.…”
Section: Discussionsupporting
confidence: 55%
“…It is known that the cholecystokinin receptor has 2 subtypes, type 1 and type 2. The expression of CCK2R (CCKBR) is greater than CCK1R in both myocardium and coronary artery10 and has a 500‐ to 1000‐fold higher affinity for gastrin than CCK1R 25, 26. In the present study, the protective effect of gastrin was abolished in the presence of a CCK2R inhibitor, CI988 (Figure 7A–7E).…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations